Leaching of crude titanium powder produced by metallothermic reduction : effects of leaching conditions on final powder quality - Sole, Kathryn (University of Pretoria, 2022)
Dissertation (MSc Applied Sciences (Metallurgy))--University of Pretoria, 2014.